Testing a Warmth-Based Instruction Intervention for Reducing Library Anxiety in First-Year Undergraduate Students - Parks, Cecelia (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – This study aimed to test the efficacy of a warmth-based library instruction intervention in reducing rates of library anxiety in first-year undergraduate students. "Warmth" is a concept that is commonly discussed within literature on library anxiety, but to date no studies have explicitly tested the application of a warmth-based instruction intervention. First-year students are ideal targets for this intervention because they are the most likely to experience library anxiety.Methods – A quasi-experiment was conducted examining library anxiety rates in first-year undergraduate students at a public research university in the U.S. South. A one-shot warmth-based instruction session focusing on the emotional dimensions of library use was compared to a standard one-shot instruction session. Library anxiety was measured using a modified version of Bostick's Library Anxiety Scale as a pretest and posttest.Results – Results indicated that both warmth-based and standard library instruction were associated with a decrease in participants' library anxiety rates without significant differences between the types of instruction. However, warmth-based instruction was correlated with greater reductions in areas of library anxiety related to interactions with library workers. Though library anxiety rates decreased significantly after experiencing library instruction, participants exhibited low levels of library anxiety before their library instruction session occurred.Conclusion – Though warmth-based instruction did not have a significantly different impact than standard library instruction on general library anxiety, the intervention tested in this study suggests strategies that could be used to increase student comfort with library workers. This study also demonstrates a successful method to include emotional factors such as library anxiety in academic libraries' regular assessment programs. Focusing assessment on students' skills and knowledge alone risks ignoring an important aspect of student engagement and missing opportunities for academic libraries to connect with students. Assessment of emotional components of library instruction initiatives is especially crucial to ensure and demonstrate that libraries are using their resources effectively to maximize student success.